2020
DOI: 10.1021/acs.jafc.0c03587
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Interactions between Epigallocatechin-3-gallate (EGCG) and Human Gut Microbiota In Vitro

Abstract: Interaction of tea phenolics with gut microbiota may play an integral role in the health benefits of these bioactive compounds, yet this interaction is not fully understood. Here, the metabolic fate of epigallocatechin-3-gallate (EGCG) and its impact on gut microbiota were integrally investigated via in vitro fermentation. As revealed by ultrahigh performance liquid chromatography hybrid quadrupole Orbitrap mass spectrometry (UHPLC-Q-Orbitrap-MS), EGCG was promptly degraded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 51 publications
2
57
0
Order By: Relevance
“…It is of note that studies reported so far in this field focused on the identification of the potential involvement of specific genera in EGCG metabolism by elucidating correlations between bacterial genera and metabolites formed. [ 25,26 ] However, detailed information on actual enzymes and pathways in the respective intestinal microbiota responsible for the EGCG conversion has not yet been elucidated and provide an interesting topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…It is of note that studies reported so far in this field focused on the identification of the potential involvement of specific genera in EGCG metabolism by elucidating correlations between bacterial genera and metabolites formed. [ 25,26 ] However, detailed information on actual enzymes and pathways in the respective intestinal microbiota responsible for the EGCG conversion has not yet been elucidated and provide an interesting topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not explore the change in the gut microbiota but highlights the potential role of commensals in breaking down green tea extracts. Furthermore, an in vitro study also investigated the metabolic fate of EGCG and its influence on gut microbiota and found that EGCG itself can be degraded into several metabolites ( 47 ). Microbiome profiling suggested that EGCG treatment increased the growth of several beneficial bacteria such as Bacteroides and Bifidobacterium and inhibited the growth of pathogenic bacteria Fusobacterium and Enterobacteriaceae ( 47 ).…”
Section: Interaction Between Dietary Polyphenols and Gut Microbiomementioning
confidence: 99%
“…Furthermore, an in vitro study also investigated the metabolic fate of EGCG and its influence on gut microbiota and found that EGCG itself can be degraded into several metabolites ( 47 ). Microbiome profiling suggested that EGCG treatment increased the growth of several beneficial bacteria such as Bacteroides and Bifidobacterium and inhibited the growth of pathogenic bacteria Fusobacterium and Enterobacteriaceae ( 47 ). On a metabolic level, 4-phenylbutyric acid was positively or negatively correlated with 11 bacterial genera ( Lachnoclostridium and Fusobacterium are positively related whereas others including Alistipes and Bacteroides are negatively correlated) ( 47 ).…”
Section: Interaction Between Dietary Polyphenols and Gut Microbiomementioning
confidence: 99%
See 2 more Smart Citations